EFEKTIVITAS STRATEGI PEMBELAJARAN BERDIFERENSIASI BERBANTUAN CERITA FILM ANAK-ANAK DALAM MENINGKATKAN KETERAMPILAN MEMIRSA SISWA KELAS V SD - Fithriya Rachmaali, Farah; Gusrayani, Diah; Djuanda, Dadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the application of differentiated learning strategies assisted by children's movie stories in improving the viewing skills of grade 5 elementary school students. The problem of this research is based on the low viewing skills of students in elementary schools and the non-optimal use of audiovisual media in Indonesian language learning. This research used quantitative method with quasi experimental design of Nonequivalent Control Group Design. The research subjects were experimental class at SDN Cikoneng 1 and control class at SDN Sukaraja 1. The research instruments included pretest and posttest tests, observation, questionnaire, and documentation. The results showed that the application of differentiated learning strategy helped by children's movie stories was significantly more effective than conventional learning in improving students' viewing skills. In addition, the implementation of this strategy also increases students' interest and participation in learning. This proves that the combination of differentiated approach and children's movie-based audiovisual media can create adaptive, interesting and appropriate learning with students' characteristics. The research found that the combination of differentiated approach and children's movie-based audiovisual media can create adaptive, interesting and appropriate learning with students' characteristics. The research findings contribute positively to the development of Indonesian language learning models based on visual literacy and provide alternative strategies to improve digital literacy skills, especially viewing skills in elementary schools.